Data-Hiding and Compression Schema Based on Image Inpainting - Akilashri, P.S.S; Kannan, B.M (International Journal of Computer Sciences and Engineering, 2025)
Digital images and videos are converted into the compressed forms for transmission. The compression and hiding the secret data in images is done because of a wide range of hackers. In order to overcome this, the messages are sent with the help of images. Many data hiding schemes have been found in the recent times with various compression techniques in digital images. Vector Quantization method help in error distortion and error diffusion which are a cause of progressive diffusion. The new idea is that one can side match vector quantization (SMVQ) and image inpainting. Data hiding and image compression can be integrated into a single module to sent the message. The receiver then finds the secret message using the image decompression technique through the index values in the segmented sections